Gd doped TiO2-NTs and Sb-SnO2 electrode material and application thereof
By combining Gd-doped TiO2 nanotubes with Sb-SnO2 to form a composite electrode material, it solves the problems of high cost and poor durability of existing electrode materials, achieves efficient removal of COD and LAS in car wash wastewater, and is suitable for other applications. Treatment of industrial wastewater.
Patent Information
- Application Number
- CN202411506880.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-24
AI Technical Summary
The existing car wash wastewater treatment technology has problems such as low treatment efficiency, complex operation, high operating cost, unstable treatment effect and secondary pollution. In particular, the high cost and low durability of electrode materials limit the application of electrochemical oxidation methods.
By introducing rare earth elements GD, the TIO2 nanotubes are doped and compounded with SB-SNO2 to form a composite electrode material of the GD doped TIO2-NTS and SB-SNO2, which improves the catalytic activity and electronic conduction capabilities of the electrode.
It significantly improves the electrochemical stability and catalytic performance of the electrode, and realizes the COD and LAS in the car washing waste water. The preparation process of the electrode material is simple, the cost is low, and it is suitable for handling industrial wastewater with other organic pollutants.
Smart Images

Figure CN119349718A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of environmental pollution control technology, and in particular to a Gd-doped TiO 2 -NTs and Sb-SnO 2 Electrode materials and their applications. Background Art
[0002] With the rapid development of urbanization and the increasing number of motor vehicles, the car wash service industry has gradually become an important part of people's daily life. However, a large amount of wastewater is generated during the car wash process. The wastewater contains sediment, oil, heavy metal ions, chemical detergents and a large amount of anionic surfactants (LAS). If these pollutants are not effectively treated and discharged directly, they will cause serious pollution to the water and soil environment.
[0003] At present, the main methods for treating car wash wastewater include physical precipitation, chemical oxidation and biological treatment. However, these traditional methods have problems such as low treatment efficiency, complex operation, high operating cost, unstable treatment effect and secondary pollution. Therefore, there is an urgent need for an efficient, economical and environmentally friendly treatment technology to solve this problem.
[0004] Electrochemical oxidation is widely used because it can effectively remove refractory organic pollutants and improve wastewater treatment efficiency. However, the selection of electrode materials plays a key role in the electrochemical treatment process. Currently, commonly used electrode materials such as platinum (Pt), ruthenium dioxide (RuO 2 ) and iridium dioxide (IrO 2 ) have high electrocatalytic activity, but their high cost and poor durability limit their practical application.
[0005] Titanium-based titanium dioxide (TiO 2 ) electrodes have been widely studied due to their good chemical stability and low cost, but their high electron-hole recombination rate limits their electrochemical performance. 2 To improve the performance of the electrode, researchers have improved TiO by doping it with rare earth elements such as Gd. 2 electronic structure and catalytic activity, thereby enhancing its ability to degrade organic pollutants.
[0006] Sb-SnO 2 The material is an ideal composite electrode material due to its strong conductivity and oxidation ability. 2 In practical applications, the material may have poor stability due to high current density. 2 Nanotubes and Sb-SnO 2The composite significantly improved the electrochemical stability and catalytic performance of the electrode, providing a new type of composite electrode material for the efficient treatment of COD and LAS in car wash wastewater. Summary of the invention
[0007] The object of the present invention is to provide a composite material capable of stably and efficiently treating organic pollutants in car wash wastewater.
[0008] In order to achieve the above object, the present invention proposes a Gd-doped TiO 2 -NTs and Sb-SnO 2 An electrode material, wherein the rare earth element Gd is introduced into the TiO 2 Nanotubes were doped with Sb-SnO 2 complex;
[0009] The electrode material is prepared by the following steps:
[0010] S1: Put the pretreated titanium material into the electrolyte and prepare Ti / TiO by anodizing 2 -NTs substrate;
[0011] S2: preparing a precursor solution containing Gd / Sn, and mixing the precursor solution and the Ti / TiO 2 -NTs substrate mixture was placed in an autoclave and subjected to solvent thermal treatment to obtain electrode A;
[0012] S3: annealing the electrode A at 450°C to 600°C to obtain Gd-doped TiO 2 -NTs / Sb-SnO 2 electrode.
[0013] Furthermore, in step S1, the titanium material is a titanium plate, and the pretreatment method of the titanium plate is: use sandpaper to grind and polish the titanium plate; put the grinded titanium plate into an acetone solution and ultrasonically clean it for 2 minutes; then soak it in a NaOH solution for 10 minutes; take out the titanium plate, rinse it with distilled water, and then put it into a 10% oxalic acid solution for micro-boiling etching for 1 hour, and ultrasonically clean it again for 10 minutes to complete the pretreatment of the titanium plate.
[0014] Furthermore, in step S1, the voltage of the anodizing treatment is 50V. After the anodizing treatment, the titanium material is placed in a muffle furnace at 450°C-500°C for calcination for 2-4 hours.
[0015] Further, in step S1, the electrolyte is NH 4 F and H 2 O ethylene glycol solution.
[0016] Further, in step S2, the precursor solution is: containing SnCl 4 ·5H 2 O、SbCl 3 and ethanolic solution of HCl.
[0017] Furthermore, in step S2, the temperature of the solvent thermal treatment is 180° C., and the treatment time is 12 hours.
[0018] Furthermore, in step S2, the molar ratio of Gd / Sn is in the range of 1:100-5:100, and the optimal molar ratio is 2:100.
[0019] Furthermore, in step S3, the optimal temperature of the annealing treatment is 600°C.
[0020] The present invention also proposes a Gd-doped TiO 2 -NTs and Sb-SnO 2 Application of Gd-doped TiO as electrode material 2 -NTs / Sb-SnO 2 The electrodes are used for COD and LAS degradation treatment of car wash wastewater, and also for industrial wastewater containing organic pollutants.
[0021] Furthermore, the Gd-doped TiO 2 -NTs / Sb-SnO 2 When the electrode is used for COD and LAS degradation treatment of car wash wastewater, the Gd-doped TiO 2 -NTs / Sb-SnO 2 The method for removing COD and LAS from car wash wastewater by electrode is as follows: the Gd-doped TiO 2 -NTs / Sb-SnO 2 The electrodes are placed in an electrolytic cell, and then the car wash wastewater stock solution is added and degraded under magnetic stirring conditions.
[0022] Compared with the prior art, the advantages of the present invention are:
[0023] 1. The present invention introduces rare earth element Gd to TiO 2 Nanotubes were doped with Sb-SnO 2 Composite to form Gd-doped TiO 2 -NTs and Sb-SnO 2 The composite electrode material effectively improves the catalytic activity and electronic conductivity of the electrode, making the electrode have high-efficiency decontamination ability, and it has excellent performance in removing COD and LAS from car wash wastewater.
[0024] 2. The present invention uses Gd-doped TiO 2Nanotubes and Sb-SnO 2 The composite not only significantly improves the catalytic activity of the electrode, but also significantly enhances the chemical and mechanical stability of the electrode, enabling it to maintain stable working performance for a long time under high current density and complex wastewater environment.
[0025] 3. The preparation process of the electrode material of the present invention is simple, easy to operate, and highly repeatable. Stable and efficient Gd-doped TiO can be prepared through conventional steps such as anodization, solvent thermal treatment, and high-temperature annealing. 2 -NTs and Sb-SnO 2 The composite electrode material effectively reduces the cost and difficulty of material preparation.
[0026] 4. The electrode material of the present invention has a wide range of applications. It not only exhibits excellent performance in the treatment of car wash wastewater, but can also be used to treat other industrial wastewater containing organic pollutants. It has broad application prospects and market value. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The Gd-doped TiO 2 -NTs and Sb-SnO 2 A schematic diagram of a method for preparing an electrode material;
[0028] Figure 2 The Ti / TiO generated by anodic oxidation in the embodiment of the present invention 2 SEM schematic diagram of nanotube array electrode substrate;
[0029] Figure 3 and Figure 4 The graphs are respectively the influence of different Gd / Sn molar ratios in the electrode materials of Examples 1-4 of the present invention on the removal effects of COD and LAS;
[0030] Figure 5 These are SEM characterization images of titanium electrode materials produced with different Gd / Sn molar ratios in Examples 1-4 of the present invention. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be further described below.
[0032] Example 1 (Gd / Sn molar ratio is 1:100)
[0033] This embodiment 1 proposes a Gd-doped TiO 2 -NTs and Sb-SnO 2 The electrode material, the preparation method thereof is as follows Figure 1 As shown, the following steps are included:
[0034] Step 1: Pre-treat the titanium plate:
[0035] 1.1: Take a pure titanium plate with a size of 20mm×20mm×1mm, and polish it with 80 mesh, 200 mesh, 600 mesh and 1000 mesh sandpaper in turn;
[0036] 1.2: Place the polished titanium plate in an acetone solution, ultrasonically clean it for 2 minutes, and then soak it in a 100 mg / L NaOH solution for 10 minutes;
[0037] 1.3: Then, the titanium plate after immersion was taken out and rinsed with distilled water, and then placed in a 10% oxalic acid solution for slight boiling etching for 1 hour, and ultrasonically cleaned again for 10 minutes: to obtain the pretreated titanium plate.
[0038] Step 2: Place the pretreated titanium plate in the electrolyte and prepare Ti / TiO by anodizing. 2 -NTs substrate, specifically:
[0039] 2.1: Place the pretreated titanium plate in 0.5wt% NH 4 F and 2 vol%H 2 O in ethylene glycol solution and anodized at 50 V for 2 h;
[0040] 2.2: After anodization, the titanium plate was calcined in a muffle furnace at 450 °C for 2 hours and then cooled naturally to obtain Ti / TiO 2 Nanotube array electrode substrate, i.e. Ti / TiO 2 -NTs substrate, the Ti / TiO 2 -SEM surface characterization of NTs substrate Figure 2 As shown, the titanium nanotubes generated by anodization are staggered and arranged neatly; the successful generation of titanium nanotubes increases the specific surface area of the titanium plate, making it easier for the titanium plate to combine with the elements in the doping solution.
[0041] Step 3: Prepare a precursor solution containing Gd / Sn and mix the precursor solution with Ti / TiO 2 -NTs substrate was mixed and placed in an autoclave for solvent thermal treatment to obtain electrode A, specifically:
[0042] 3.1: Dissolve 2.625g SnCl in 75mL ethanol 4 ·5H 2 O, 0.1725 g SbCl 3 and 6.3 mL of concentrated HCl, stir well;
[0043] 3.2: Add 0.0338 g Gd(NO 3 ) 36H 2 O, obtaining a precursor solution, wherein the molar ratio of Gd / Sn in the precursor solution is 1:100;
[0044] 3.3: Mix the precursor solution with Ti / TiO 2 -NTs substrate were placed in an autoclave and heated at 180°C for 12 hours. After heating, they were cooled to room temperature to obtain electrode A and taken out;
[0045] Step 4: Rinse the motor A with deionized water, air-dry it, and then anneal it at 600°C for 3 hours to obtain the Gd-doped TiO 2 -NTs / Sb-SnO 2 electrode.
[0046] Example 2 (the molar ratio of Gd / Sn is 2:100)
[0047] This embodiment 2 proposes a Gd-doped TiO 2 -NTs and Sb-SnO 2 The electrode material is prepared in the same manner as in Example 1, except that the molar ratio of Gd / Sn is different. In step 3 of Example 2, step 3.2 is: adding 0.0675 g of Gd(NO 3 ) 3 6H 2 O to obtain a precursor solution, and the molar ratio of Gd / Sn in the precursor solution is 2:100.
[0048] Example 3 (the molar ratio of Gd / Sn is 3:100)
[0049] This embodiment 3 proposes a Gd-doped TiO 2 -NTs and Sb-SnO 2 The electrode material is prepared in the same manner as in Example 1, except that the molar ratio of Gd / Sn is different. In step 3 of this Example 3, step 3.2 is: adding 0.1013 g of Gd(NO 3 ) 3 6H 2 O to obtain a precursor solution, and the molar ratio of Gd / Sn in the precursor solution is 3:100.
[0050] Example 4 (the molar ratio of Gd / Sn is 5:100)
[0051] This embodiment 4 proposes a Gd-doped TiO 2 -NTs and Sb-SnO 2The electrode material is prepared in the same manner as in Example 1, except that the molar ratio of Gd / Sn is different. In step 3 of this Example 4, step 3.2 is: adding 0.1686 g of Gd(NO 3 ) 3 6H 2 O to obtain a precursor solution, and the molar ratio of Gd / Sn in the precursor solution is 5:100.
[0052] Observe the SEM characterization images of the titanium electrode materials generated by different Gd / Sn molar ratios in the above-mentioned Examples 1, 2, 3 and 4, as shown in FIG. Figure 5 As shown, the Sb-SnO of the titanium electrode plate after the doping process 2 The oxide layers all present a spherical stacked cluster film structure, and when the Gd / Sn ratio is 2:100, the electrode morphology is relatively dense and the particles are small, which is conducive to resisting electrochemical corrosion and can extend the service life of the electrode. At the same time, the increase in the size of small particles can provide a larger surface area, thereby providing more catalytic active sites. When the molar ratio of Gd doping increases to 3:100 and 5:100, the oxide layer shows obvious aggregation.
[0053] In addition, taking the car wash wastewater as an example, the following degradation experiments were carried out:
[0054] The above-mentioned Example 1, Example 2, Example 3 and Example 4 were placed in the same electrolytic cell, and the same amount of car wash wastewater stock solution was added respectively. The degradation experiment was carried out under the same magnetic stirring conditions. The experimental results are as follows: Figure 3 and Figure 4 As shown:
[0055] The electrode material of Example 1 has a COD removal rate of 45.1% and a LAS removal rate of 67.2%;
[0056] The electrode material of Example 2 has a COD removal rate of 71.7% and a LAS removal rate of 72.6%;
[0057] The electrode material of Example 3 has a COD removal rate of 63.7% and a LAS removal rate of 68.3%;
[0058] The electrode material of Example 4 has a COD removal rate of 33.4% and a LAS removal rate of 54.8%;
[0059] It can be seen that when the molar ratio of Gd / Sn is 2:100, the Gd-doped TiO 2 -NTs and Sb-SnO 2 The electrode material has the best effect on the degradation of COD and LAS in car wash wastewater.
[0060] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any technician in the relevant technical field, without departing from the scope of the technical solution of the present invention, makes any form of equivalent replacement or modification to the technical solution and technical content disclosed in the present invention, which does not depart from the content of the technical solution of the present invention and still falls within the protection scope of the present invention.
Claims
1. An electrode material of Gd-doped TiO2-NTs and Sb-SnO2, characterized in that: Rare earth element Gd is introduced to dope TiO2 nanotubes and composite them with Sb-SnO2; the electrode material is prepared by the following steps: S1: placing the pretreated titanium material into an electrolyte and preparing a Ti / TiO2-NTs substrate by anodizing; S2: preparing a precursor solution containing Gd / Sn, and mixing the precursor solution and the Ti / TiO2-NTs substrate into an autoclave for solvent thermal treatment to obtain electrode A; S3: Annealing the electrode A at 450° C. to 600° C. to obtain a Gd-doped TiO2-NTs / Sb-SnO2 electrode.
2. The electrode material of Gd-doped TiO2-NTs and Sb-SnO2 according to claim 1, characterized in that: In step S1, the titanium material is a titanium plate, and the pretreatment method of the titanium plate is: use sandpaper to grind and polish the titanium plate; put the polished titanium plate into an acetone solution and ultrasonically clean it for 2 minutes; then put it into a NaOH solution and soak it for 10 minutes; take out the titanium plate and rinse it with distilled water, then put it into a 10% oxalic acid solution and etch it with micro-boiling for 1 hour, and ultrasonically clean it again for 10 minutes to complete the pretreatment of the titanium plate.
3. The electrode material of Gd-doped TiO2-NTs and Sb-SnO2 according to claim 1, characterized in that: In step S1, the voltage of the anodizing treatment is 50V. After the anodizing treatment, the titanium material is placed in a muffle furnace at 450°C-500°C for calcination for 2-4 hours.
4. The electrode material of Gd-doped TiO2-NTs and Sb-SnO2 according to claim 1, characterized in that: In step S1, the electrolyte is NH4F and H2O ethylene glycol solution.
5. The electrode material of Gd-doped TiO2-NTs and Sb-SnO2 according to claim 1, characterized in that: In step S2, the precursor solution is: an ethanol solution containing SnCl4·5H2O, SbCl3 and HCl.
6. The electrode material of Gd-doped TiO2-NTs and Sb-SnO2 according to claim 1, characterized in that: In step S2, the temperature of the solvent thermal treatment is 180° C. and the treatment time is 12 hours.
7. The electrode material of Gd-doped TiO2-NTs and Sb-SnO2 according to claim 1, characterized in that: In step S2, the molar ratio of Gd / Sn is in the range of 1:100-5:100, and the optimal molar ratio is 2:
100.
8. The electrode material of Gd-doped TiO2-NTs and Sb-SnO2 according to claim 1, characterized in that: In step S3, the optimum temperature for the annealing treatment is 600°C.
9. An application of the electrode material of Gd-doped TiO2-NTs and Sb-SnO2 as claimed in any one of claims 1 to 8, characterized in that: The Gd-doped TiO2-NTs / Sb-SnO2 electrode is applied to the COD and LAS degradation treatment of car wash wastewater, and is also applied to industrial wastewater containing organic pollutants.
10. The use of the electrode material of Gd-doped TiO2-NTs and Sb-SnO2 according to claim 9, characterized in that: When the Gd-doped TiO2-NTs / Sb-SnO2 electrode is used for COD and LAS degradation treatment of car wash wastewater, the method for removing COD and LAS from car wash wastewater by the Gd-doped TiO2-NTs / Sb-SnO2 electrode is as follows: placing the Gd-doped TiO2-NTs / Sb-SnO2 electrode in an electrolytic cell, adding car wash wastewater stock solution, and performing degradation under magnetic stirring conditions.
Citation Information
Patent Citations
Preparation method of novel titanium-based SnO2 anode
CN117509832A
Rare-earth doped titanium-base SnO2 electrolytic electrode and its preparation
CN1896320A
Water recycling equipment with electrolysis UV (ultraviolet) light contact agent
CN201817306U
Car washing wastewater treatment process system
CN208454729U
Method for manufacturing manganese-doped titaniumoxide nanotube using anodic oxidation and manganese-doped titaniumoxide nanotube
KR102047528B1